2010
DOI: 10.1210/en.2010-0116
|View full text |Cite
|
Sign up to set email alerts
|

An Inositol 1,4,5-Triphosphate (IP3)-IP3 Receptor Pathway Is Required for Insulin-Stimulated Glucose Transporter 4 Translocation and Glucose Uptake in Cardiomyocytes

Abstract: Intracellular calcium levels ([Ca2+]i) and glucose uptake are central to cardiomyocyte physiology, yet connections between them have not been studied. We investigated whether insulin regulates [Ca2+]i in cultured cardiomyocytes, the participating mechanisms, and their influence on glucose uptake via SLC2 family of facilitative glucose transporter 4 (GLUT4). Primary neonatal rat cardiomyocytes were preloaded with the Ca2+ fluorescent dye fluo3-acetoxymethyl ester compound (AM) and visualized by confocal microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…In this context, our group has previously demonstrated that inhibition of InsP 3 R with XeC and the Ca 2+ chelating agent BAPTA-AM also reduces Akt phosphorylation [19]. Moreover, we showed that the induction of mitochondrial fragmentation reduces insulin-induced Akt phosphorylation by reducing mitochondrial Ca 2+ uptake [35].…”
Section: Mitochondrial Insulin-dependent Ca 2+ Signals In Hypertrophimentioning
confidence: 80%
See 1 more Smart Citation
“…In this context, our group has previously demonstrated that inhibition of InsP 3 R with XeC and the Ca 2+ chelating agent BAPTA-AM also reduces Akt phosphorylation [19]. Moreover, we showed that the induction of mitochondrial fragmentation reduces insulin-induced Akt phosphorylation by reducing mitochondrial Ca 2+ uptake [35].…”
Section: Mitochondrial Insulin-dependent Ca 2+ Signals In Hypertrophimentioning
confidence: 80%
“…Ca 2+ has also been identified as an important second messenger acting downstream of the insulin receptor and shown to be essential in insulin-mediated glucose uptake in cardiac and skeletal muscle [38][39][40]. Our group showed that Ca 2+ release from the ER through the InsP 3 R is an important component of the Ca 2+ -mediated insulin response in cardiomyocytes [19]. Mitochondria have a substantial capacity for Ca 2+ storage that is facilitated by their physical and functional interaction with InsP 3 Rs in the ER membrane [41].…”
Section: Discussionmentioning
confidence: 91%
“…Images were collected for 10 min using laser scanning confocal microscope in the frame-by-frame mode as previously reported (Contreras-Ferrat et al, 2010). L6 myotubes were preloaded with Fluo4 am (5 mM) at 37˚for 30 min in Krebs Ringer buffer and stimulus were added to the microscopy chamber as indicated by arrows.…”
Section: Intracellular Ca 2+ Measurementsmentioning
confidence: 99%
“…A recent report proposes that RyR1 channels, by controlling passive Ca 2+ efflux from the SR to the cytoplasm, represent key factors in the management of the resting muscle cytoplasmic Ca 2+ concentration (Eltit et al, 2010). Interestingly, our groups have reported that: (1) insulin elevates intracellular Ca 2+ levels via NOX2 activation in primary neonatal myotubes (Espinosa et al, 2009), (2) NOX2-dependent ROS production promotes RyR1 S-glutathionylation and stimulates RyR1-mediated Ca 2+ release from triad-enriched vesicles isolated from adult skeletal muscle , and (3) intracellular Ca 2+ contributes to the insulin-dependent increase in glucose uptake in cardiomyocytes (Contreras-Ferrat et al, 2010). The physiological mechanism whereby insulin activates NOX2, however, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Since the identification of PKB as a serine/threonine kinase, almost 20 years ago, PKB isoforms were studied intensively and are now considered as major regulators of elementary cellular process, such as proliferation, survival, cell growth and energy metabolism (Bozulic et al, 2008, Contreras-Ferrat et al, 2010, Haga et al, 2005, Heron-Milhavet et al, 2006. Consequently, PKB isoforms play pivotal roles in physiology and their deregulation engenders diseases, such as cancer, neurodegeneration and metabolic disorders (Altomare andTesta, 2005, Zhao andTownsend, 2009).…”
Section: Protein Kinase Bmentioning
confidence: 99%